Awareness and understanding of concussion among Aboriginal Australians with high health literacy - Trish Hill-Wall; Kahlia McCausland; Elizabeth Thomas; Richard Norman; Jonathan Bullen; Gill Cowen (Concussion, 2024)
Aim: Indigenous Australians have higher rates of traumatic brain injury,with 74–90% of such injuries being concussion. This study explores concussion awareness and knowledge in Aboriginal Western Australians with high health literacy. Materials & methods: Participants, aged 18–65 years, engaged in research topic yarning, and thematic analysis of the qualitative data then undertaken. Results: There was awareness that direct head trauma can result in concussion, but a lack of differentiation between concussion and other head injuries. Knowledge was gained from sport, media or lived-experience. Symptom minimization and diversity of concussion symptoms prevented participants from seeking medical treatment. This was exacerbated by a mistrust of the medical system. Conclusion: Research findings highlight knowledge and service gaps where co-designed strategies can be targeted.